2010
DOI: 10.1111/j.1745-4514.2009.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and Traditional Cooking Methods: Effect of Cooking on Antioxidant Capacity and Phenolic Compounds Content of Seven Vegetables

Abstract: The effect of microwave, boiling and pressure cooking on total antioxidant capacity and total phenolics content of seven vegetables were studied. Total phenolics in raw and cooked vegetables were determined by the Folin–Ciocalteu method, whereas the total antioxidant capacity of vegetables extracts was evaluated using the Crocin method. After boiling, four out of seven vegetables (cauliflower, peas, spinach and Swiss chard) showed a significant decrease in their total phenolic content (P < 0.05). No decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
6
22
0
Order By: Relevance
“…Total phenolics were retained at only 58% in spinach microwaved at 800 W. 78 Total phenolics content was generally more degraded after boiling than microwaving. Microwaving resulted in higher levels of minerals in spinach as compared to cooking in boiling water for the following: ash, P, K, Ca, Mg, Na, Fe, Zn, Mn, Cu (all but C and Ni, which were same as boiling).…”
Section: Spinachmentioning
confidence: 90%
See 2 more Smart Citations
“…Total phenolics were retained at only 58% in spinach microwaved at 800 W. 78 Total phenolics content was generally more degraded after boiling than microwaving. Microwaving resulted in higher levels of minerals in spinach as compared to cooking in boiling water for the following: ash, P, K, Ca, Mg, Na, Fe, Zn, Mn, Cu (all but C and Ni, which were same as boiling).…”
Section: Spinachmentioning
confidence: 90%
“…Picouet et al 65 found that the total phenolics content in apple purée was similar before and after microwaving. Carrot, cauliflower, pea, potato, spinach, Swiss chard and tomato were studied by Natella et al 78 and results were reported on a dry weight basis. Total phenolics were retained at 104-125% in all of the microwaved vegetables except peas (39% loss) and spinach (42% loss).…”
Section: Total Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Farah et al, (Farah et al, 2005) reported that the amount of total 3-CQA and 3-CQA lactones from coffee decreased to less than 5.2% and 20%, respectively, of their maximal values at a longer time of roasting. Comparable findings reported that the total phenol content in various vegetables was shown to have a decreasing tendency after boiling (Natella et al, 2010). …”
Section: Effect Of Various Cooking Methods On Content Of Cqas From Gomentioning
confidence: 71%
“…The total flavonoid, phenolic content, and antioxidant activity was reduced in cooked green beans at 100-120°C for 10-40 min ( Jiratanan and Liu, 2004). Microwave cooking may retain or decrease the phytochemical content in spinach, cauliflower, and peas as compared to boiling (Natella et al, 2010). Antioxidant activity of spinach, garlic, maize, onion, pepper, and Swiss chard was increased after microwave cooking ( Jim enez-Monreal et al, 2009).…”
Section: Cookingmentioning
confidence: 99%